What are the motives underlying Brazilians' food choices? An analysis of the Food Choice Questionnaire and its relationship with different sample characteristics - da Silva, Wanderson Roberto [UNESP]; Marôco, João; Alvarenga, Marle dos Santos; Campos, Juliana Alvares Duarte Bonini [UNESP] (Wiley, 2022)
The first aim of this study was to evaluate the psychometric properties of the Food Choice Questionnaire (FCQ)—using the original model—in a sample of 1480 Brazilian adults (69.5% female). The second aim was to rank the reasons underlying the participants' food choices using average FCQ scores and 95% confidence interval. The third aim was to evaluate the relationship between food choice motives and sample characteristics using multiple logistic regression and odds ratios. The validity, the invariance across different groups, and the reliability of the FCQ were confirmed for the sample. Sensory appeal and price emerged as the most important reasons, while ethical concern was the least valued. The factors associated with greater odds of choosing food for specific reasons were being older, female, and a student; practicing physical activity; dieting frequently; self-rating eating quality as good; having a higher body mass index; and having low income. Practical Applications: Assessing food choice is a complex task, as it encompasses several factors, such as sensory characteristics, health status, income, culture, lifestyle, and cognitive-affective issues; therefore, the use of appropriate tools should be encouraged. The set analyses followed confirmed that the FCQ was an adequate instrument to evaluate the reasons for food choice of the participants who valued strongly the sensory aspects of the foods and presented specific characteristics (e.g., diet practice) that may influence their decisions. These findings may guide future research and clinical interventions aimed at producing food choices that are more oriented to health and well-being.